Mitigation Strategies and Economic Potential of Waste Resource Recovery in Banjarbaru City, South Kalimantan - Rudy Heryadi; Fujianor Maulana; Difo Miftahul Faridl; Hendera (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The global challenge of municipal solid waste management (MSW) has reached a critical turning point, requiring urgent action from cities worldwide. Banjarbaru, Indonesia, as the dynamic capital of South Kalimantan, also needs to take action to address MSW-related problems. Official data indicate that approximately 191 tonnes of MSW are generated per day, and this amount will increase exponentially as the city grows. This study aims to project waste generation through 2030, identify waste recovery strategies focused solely on organic waste and high-value recyclables, and assess their economic potential. The method used in this study is the bottom-up estimation method, which is the standard for waste management feasibility studies. Waste generation is projected to grow exponentially to approximately 257 tonnes per day by 2030. There is a lucrative annual revenue stream of IDR 30.6 billion from improved waste management in Banjar Baru, South Kalimantan. This potential can serve as an alternative to the waste management challenge and help transform it into a circular economy model.